2000
DOI: 10.1094/cchem.2000.77.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Kernel Size to Flour Water Absorption for Canada Western Red Spring Wheat

Abstract: Canada Western Red Spring (CWRS) wheat exhibits consistent positive relationships between kernel weight and farinograph and baking water absorption. These relationships are sufficiently robust to be statistically significant (P < 0.05) for historical Canadian Grain Commission harvest survey data generated one year apart for 17 years, and for historical data on individual cultivars in advanced Canadian wheat breeding trials, also generated annually. Verification of the relationships were obtained by analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
2
14
0
1
Order By: Relevance
“…There were also significant relationships between these physical properties in Korean wheats. Those results are in good agreement with previous results (Bettege and Morris 2000, Morgan et al 2000, Martin et al 2001, Nagamine et al 2003, Zhang et al 2005, Chen et al 2007. Therefore, grain characteristics, especially hardness index of grain, could have influence on the milling performance and physical properties of Korean wheat flours.…”
Section: Discussionsupporting
confidence: 92%
“…There were also significant relationships between these physical properties in Korean wheats. Those results are in good agreement with previous results (Bettege and Morris 2000, Morgan et al 2000, Martin et al 2001, Nagamine et al 2003, Zhang et al 2005, Chen et al 2007. Therefore, grain characteristics, especially hardness index of grain, could have influence on the milling performance and physical properties of Korean wheat flours.…”
Section: Discussionsupporting
confidence: 92%
“…Water absorption of flour increases with increasing wheat kernel thickness, which agrees with the results of Morgan et al (2000), and it increases with decreasing specific density. Water absorption of wheat flour for unfractionated soft wheat and fractionated soft wheat with the several different kernel thicknesses is correspondingly lower than that for unfractionated hard wheat and fractionated hard wheat with different kernel thicknesses.…”
Section: Rheological Properties Of Doughssupporting
confidence: 88%
“…Morgan et al (2000) reported that "in general, as kernel size declines, flour yield and flour refinement (ash and color) are adversely affected". Morgan et al (2000) observed highly significant positive relationships between kernel size and farinograph and baking water absorption. Morgan et al (2000) observed highly significant positive relationships between kernel size and farinograph and baking water absorption.…”
mentioning
confidence: 99%
“…The milling and baking properties of smaller kernels were not found to be inferior to larger counterparts, but were equivalents. Aversely, Morgan et al [37] reported that "in general, as kernel size declines, flour yield and flour refinement (ash and color) are adversely affected", but agrees that small kernels were softer than large kernels.…”
Section: Axial Dimensionsmentioning
confidence: 99%